Yellow fever in Brazil: thoughts and hypotheses on the emergence in previously free areas - Pedro Fernando da Costa Vasconcelos (Universidade de São Paulo, 2010)
This article describes and discusses factors associated to the reemergence of yellow fever and its transmission dynamics in the states of São Paulo (Southeastern Brazil) and Rio Grande do Sul (Southern) during 2008 and 2009. The following factors have played a pivotal role for the reemergence of yellow fever in these areas: large susceptible human population; high prevalence of vectors and primary hosts (non-human primates); favorable climate conditions, especially increased rainfall; emergence of a new genetic lineage; and circulation of people and/or monkeys infected by virus. There is a need for an effective surveillance program to prevent the reemergence of yellow fever in other Brazilian states.